The endless song - Johnson, Joshua Phillip (Johnson, Joshua Phillip. Tales of the forever sea., 2023)
Kindred Greyreach, at odds with a faction below the Sea, must use every power to forestall disaster, while, above, a boy named Flitch finds himself caught in a dangerous political crisis, and they must work together to save themselves, their loved ones, and the Forever Sea itself.